2019
DOI: 10.2134/agronj2019.05.0336
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Fertilization for Fresh Market Potato Production in Tropical Soils

Abstract: Potassium (K) is the most taken up and removed nutrient by potato (Solanum tuberosum L.), and has a great influence on tuber yield and quality. This study was performed to evaluate the effects of three rates (100, 200, and 400 kg K2O ha−1) and two timings of application of K (single application at planting furrow and split application of 50% at planting furrow plus 50% at hilling), as potassium chloride, as well as a control (without K application) on the plant nutrition and tuber yield and quality of potato ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
(107 reference statements)
0
8
0
2
Order By: Relevance
“…Potatoes (Solanum tuberosum L) are an important staple crop in most parts of the world. They have high nutrient requirements, among which potassium (K) is required in higher concentrations than both nitrogen and phosphorus (Fernandes et al 2017;Job et al 2019). Fernandes et al (2017), when comparing five potato cultivars under different phosphorus supplies, showed that the N, P and K in the whole plant dry matter varied between 1.58-2.16, 0.18-0.26 and 2.93-3.78%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potatoes (Solanum tuberosum L) are an important staple crop in most parts of the world. They have high nutrient requirements, among which potassium (K) is required in higher concentrations than both nitrogen and phosphorus (Fernandes et al 2017;Job et al 2019). Fernandes et al (2017), when comparing five potato cultivars under different phosphorus supplies, showed that the N, P and K in the whole plant dry matter varied between 1.58-2.16, 0.18-0.26 and 2.93-3.78%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a high amount of K fertilizers is usually required to obtain high potato crop yields probably due to the low nutrient uptake efficiency of potato crops due to their small root systems (Iwama 2008;Sandaña 2016). However, tuber yield responses to K fertilization depend on the initial level of soil K availability (Birch et al 1967;Allison et al 2001;Li et al 2015;Job et al 2019). Nonetheless, farmers did not know how much K should be applied due to the lack of information regarding the critical level of soil K for potato crops (Li et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, rates higher than those reported by Abdelgadir et al [72] are commonly applied by potato farmers/producers. Furthermore, Job et al [89] reported that the maximum tuber yield was obtained with an estimated fertilization rate of 325 kg of K2O ha −1 in a soil with low exchangeable K (27 mg kg −1 ), while the tuber yield increased only up to the rate of 200 kg K2O ha −1 in the soils with 62 and 144 mg kg −1 exchangeable soil K. In this regard, several researchers revealed that most vegetative parameters, as well as Sharma and Sud [79] conducted studies on acidic and alluvial soils and showed that K 2 SO 4 was superior to KCl in increasing tuber dry matter, ascorbic acid, and starch content. Indeed, K 2 SO 4 is a readily plant-available form of K [80] and this could explain the faster translocation of photosynthates from leaves and stems to tubers under fertilization with K 2 SO 4 compared to KCl [69].…”
Section: Effects Of K Ratementioning
confidence: 99%
“…Nonetheless, rates higher than those reported by Abdelgadir et al [72] are commonly applied by potato farmers/producers. Furthermore, Job et al [89] reported that the maximum tuber yield was obtained with an estimated fertilization rate of 325 kg of K 2 O ha −1 in a soil with low exchangeable K (27 mg kg −1 ), while the tuber yield increased only up to the rate of 200 kg K 2 O ha −1 in the soils with 62 and 144 mg kg −1 exchangeable soil K. In this regard, several researchers revealed that most vegetative parameters, as well as yield and its components, increased significantly when K fertilization rates increased from 120 to 240 kg K 2 O ha −1 [28,64]. Singh and Singh [90] observed a noteworthy increase in plant height and shoot biomass of potato as K fertilization rates increased from 50 to 200 kg K 2 O ha −1 .…”
Section: Effects Of K Ratementioning
confidence: 99%
“…Estudos prévios com fracionamento da fertilização em diversas culturas mostraram que uma parte do nutriente deve ser aplicado no plantio para maximizar a produtividade (CORRÊA et al, 2018;LUO;LI, 2018;MAROUELLI et al, 2015). No entanto, a fertilização de K feita somente no plantio pode causar salinização e prejudicar a absorção de outros nutrientes (JOB et al, 2019). Neste estudo não foi adotado fertilização de K totalmente no plantio.…”
Section: Discussionunclassified